Manejo do crestamento bacteriano comum do feijoeiro por Rhodotorula Glutinis e Sporidiobolus johnsonii - Carvalho, Jeferson Carlos (2017)
Common bacterial blight of beans reduces crop yields and is difficult to control. Biological control using yeasts might be an alternative. It was aimed to evaluate the capacity of Rhodotorula glutinis and Sporidiobolus johnsonii to reduce the severity of common bacterial blight of beans and to act as plant growth stimulator, as well as to determine the appropriate dose and number of applications for phytosanitary treatment. The yeast R. glutinis (AH 14-3) was isolated from roses and S. johnsonii (AH 16-1) was obtained from touch-me-not leaves (Impatiens walleriana). Four experiments were carried out using the cultivar IAPAR Tuiuiu. Two of them were held in a greenhouse, one to determine the best dose (0; 2,5; 5; 7,5; and 10 g L-1 of R. glutinis and S. johnsonii, along with a commercial dose of acibenzolar-S-methyl (ASM)) and another to determine the level of applications during the cultivation cycle (zero, one, two, and three applications of R. glutinis and S. johnsonii (5 g L-1) and ASM (25 g L-1)). In both experiments, the area under the disease progress curve (AUDPC), the dry mass of the aerial part (DMAP), the dry mass of root (DMR) and root volume (RV) were evaluated. The other two experiments were carried out under seeded-field conditions in March and in October, with a 4X3 factorial arrangement (zero, one, two and three applications and three R. glutinis, S. johnsonii and ASM treatments). Under these conditions, were evaluated AUDPC, number of pods per plant (NPP), number of seeds per pod (NSP), one thousand seed mass (TSM) and yield. For doses, the isolate of S. johnsonii reduced the AUDPC by 59,61% on a dose-dependent basis, reaching the value of 14,61 at a dose of 10 g L-1, similar to ASM (14,31). On the other hand, the isolate of R. glutinis did not affect the AUDPC. The yeasts stimulated plant growth at a dose of 5 g L -1. Regarding the number os applications in a greenhouse, R. glutinis reduced the progress of the disease by 62,73% after two applications, whereas the isolate S. johnsonii presented a linear effect, with a reduction of 49,88% after three applications, and the number of applications did not interfere in growth variables. Concerning the results of autumnwinter cultivation, in the AUDPC the isolates R. Glutinis and S. johnsonii did not present any difference between them, 17,28 and 19,14, respectively, independently of the number of applications, however ASM showed the greatest severity with two applications. For productivity, the isolate R. glutinis showed the highest average, 1006,44 kg ha-1, with two applications. For cultivation in water, the isolates R. glutinis and S. johnsonii reduced the AUDPC by 66,84% and 58,42%, respectively, with three applications. For productivity, R. glutinis and S. johnsonii did not present any difference between the number of applications, with averages of 3708,96 and 3896,71, respectively. ASM caused a linear increase in production, 4418,56 kg ha-1 after three applications. Results reveal that yeasts R. glutinis and S. johnsonii reduce the severity of common bacterial blight of beans and have the ability to stimulate plant growth. The best dose is 5 g L-1 and it is more effective with two applications. Keywords: Biological control. Fabaceae. Phaseolus vulgaris L. Xanthomonas axonopodis pv. Phaseoli. Production.